2011
DOI: 10.1159/000323300
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Thyroid Carcinoma: An Easy Fine Needle Aspiration Biopsy Diagnosis?

Abstract: Objective: To analyze reasons for unclear or missed diagnoses in fine needle aspiration biopsy (FNAB) of papillary thyroid carcinoma (PTC). Study Design: Among 35,000 thyroid FNAB diagnoses made during 1989–2009, 135 PTC FNAB diagnoses were divided into 3 categories by expressed probability. A group of 10 cases with histologic PTC diagnosis not mentioned in our previous FNAB sample was also analyzed. Results: Of the 75 PTC FNAB diagnoses, 71 were confirmed; the remaining 4 were hyperplastic goiters. In the gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 163 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…Recently, a report was published to analyze reasons for missed diagnoses in the FNA of PTC. The authors of this study concluded that FNA for the diagnosis of PTC is not always possible, and several factors, including tumor size, associated lymphocytic thyroiditis, and the representativeness of cytology samples, will influence the diagnostic success rate of PTC [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, a report was published to analyze reasons for missed diagnoses in the FNA of PTC. The authors of this study concluded that FNA for the diagnosis of PTC is not always possible, and several factors, including tumor size, associated lymphocytic thyroiditis, and the representativeness of cytology samples, will influence the diagnostic success rate of PTC [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Low-risk tumours (NIFTP, follicular tumours with unclear malignant potential -FT UMP, WDT UMP and hyalinizing trabecular tumour -HTT) have a low risk of malignancy and are not considered carcinomas, but neoplasms 4,24,27 . However, suspicion regarding these tumours requires surgical intervention (hemithyroidectomy), and a detailed histopathological examination is necessary to establish a definitive diagnosis, which is very difficult at the cytological level 4,23 . These tumours are very often cytologically classified as indeterminate -Bethesda III (31%) or Bethesda IV (26.6 %) (ref.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is an effort to develop combined testing using new generation sequencing methods (NGS), e. g. Thyroseq panel 3,5,13 , but these tests are not available in the Czech Republic. The treatment of indeterminate nodules includes both non-surgical methods such as clinical and USG followup, repeated US-FNA (US-guided fine-needle aspiration) after 6 months 11,21 , molecular genetic testing, and surgical methods such as diagnostic or therapeutic surgery and histopathological examination 12,22,23 .…”
Section: Introductionmentioning
confidence: 99%